Characterization of Volatile Compounds of Selected Aromatic Plants from West Java (Al-Kimia, 2025)
Chrysopogon zizanioides (Poaceae), Pogostemon cablin (Lamiaceae), Cymbopogon nardus (Poaceae) and Citrus reticulate (Rutaceae) are known for their abundant essential oils and major commodities in Garut, West Java. Understanding the chemical composition of organic compounds can provide insights into the complex mixture of organic compounds contributing in plants' odour, flavour, and potency. This study aimed to identify the chemical composition of the essential oils of C. zizanioides (roots), P. cabin (leaves), C. nardus (stems), and C. reticulate (leaves and peel). The essential oils were distilled using the hydro distillation method. The chemical composition of essential oils was analyzed by Gas Chromatography-Massa Spectrometry (GC-MS). The results showed that the dominant significant compounds in the essential oil of C. zizanioides roots included valerenal (14.81%). Patchouli alcohol (33.23%) and E-citral (36.18%) were found in P. cabin leaves and C. nardus stems, respectively. The essential oil of C. reticulate leaves and peel contained significant compounds, namely limonene, with a percentage of 30.98% for leaves and 82.58% for peel. Sesquiterpenes were the dominant compounds found in C. zizanioides root and P. cabin leaves oil, while monoterpenes were the major compounds in C. nardus stem, C. reticulate leaves and peel.